2017
DOI: 10.3389/fnins.2017.00161
|View full text |Cite
|
Sign up to set email alerts
|

Present Molecular Limitations of ON-Bipolar Cell Targeted Gene Therapy

Abstract: Recent studies have demonstrated the safety and efficacy of ocular gene therapy based on adeno-associated viral vectors (AAVs). Accordingly, a surge in promising new gene therapies is entering clinical trials, including the first optogenetic therapy for vision restoration. To date, optogenetic therapies for vision restoration target either the retinal ganglion cells (GCs) or presynaptic ON-bipolar cells (OBCs). Initiating light responses at the level of the OBCs has significant advantages over optogenetic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 26 publications
1
51
0
Order By: Relevance
“…This was the first demonstration of robust bipolar cell transduction from an AAV vector but transduction in a wild type mouse does not necessarily translate to degenerate retina or indeed non-human primate and human retina. Further confirmation of human bipolar cell transduction was provided in a later study using human retinal explants that also showed targeting of cone ON-bipolar cells by a reporter AAV8(BP2) vector (van Wyk et al, 2017). This study showed comparable human bipolar cell expression patterns were achieved from both AAV8(BP2) and AAV2(7m8) vectors and also performed similarly in the degenerate 11-week-old rd10 mice.…”
Section: Cell-specific Targeting In the Degenerate Retina Vector Conssupporting
confidence: 54%
See 1 more Smart Citation
“…This was the first demonstration of robust bipolar cell transduction from an AAV vector but transduction in a wild type mouse does not necessarily translate to degenerate retina or indeed non-human primate and human retina. Further confirmation of human bipolar cell transduction was provided in a later study using human retinal explants that also showed targeting of cone ON-bipolar cells by a reporter AAV8(BP2) vector (van Wyk et al, 2017). This study showed comparable human bipolar cell expression patterns were achieved from both AAV8(BP2) and AAV2(7m8) vectors and also performed similarly in the degenerate 11-week-old rd10 mice.…”
Section: Cell-specific Targeting In the Degenerate Retina Vector Conssupporting
confidence: 54%
“…A comparison of multiple copies of the Grm6 enhancer identified that including four copies prior to the SV40 promoter improved reporter gene expression (Cronin et al, 2014). Whilst this promoter has been shown to primarily enable transgene expression in ON-bipolar cells, expression has been identified in other cell types (van Wyk et al, 2015(van Wyk et al, , 2017. The expression profile of an optogenetic transgene with fluorescent reporter revealed predominant expression in amacrine cells and a lack of ON-bipolar cell targeting in rd1 mice.…”
Section: Transgene Considerationsmentioning
confidence: 99%
“…In the outer retina, we found that Cbh and Ubiquitin (Matsuda and Cepko, 2004) regulatory elements drive expression of fluorescent reporters in Rods, Bipolar Cells and Muller Glia. We used a 2.3 kb fragment of the Rhodopsin promoter to drive Cas9 expression in rods (Matsuda and Cepko, 2004; 2007), and a 1082 bp fragment containing a tandem repeat of an mGluR6-SV40 promoter (4XGrm6-Sv40) from the pAAV-4xGRM6-CatCh-EGFP vector (gift from Botand Roska) to drive Cas9 expression in ON BCs (van Wyk et al, 2017). Promoters were cloned between the KpnI and AgeI restriction sites in px458.…”
Section: Star Methodsmentioning
confidence: 99%
“…AAV never achieves complete infection and is normally “patchy,” so complete restoration of a receptive field looks unlikely. Furthermore, the mGluR6 promoters used to restrict expression to the ON-bipolar cells may not work in many retinal dystrophies due to dis- and downregulation of mGluR6 (van Wyk et al, 2017 ). mGluR6 is tonically activated by the continuous release of glutamate by photoreceptors in the dark.…”
Section: Delivery Methodsmentioning
confidence: 99%